2015
DOI: 10.1002/eji.201445219
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of TLR2 in CD4+ T cells from SLE patients enhances immune reactivity and promotes IL‐17 expression through histone modifications

Abstract: The innate immune system has been shown to play an important pathologic role in systemic lupus erythematosus (SLE). TLR2, a PRR, recognizes exogenous PAMPs, and endogenous damage-associated molecular patterns and has been implicated in the initiation and maintenance of the perpetuated inflammatory reactions in autoimmune diseases. Here, we report increased expression of TLR2 in CD4+ and CD8 + T cells, CD19 + B cells, and CD14 + monocytes from SLE patients. Conventional treatment, such as hydroxychloroquine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 37 publications
(44 reference statements)
1
34
0
1
Order By: Relevance
“…2). Stimulation of SLE T cells through TLR2, a molecule increased in SLE CD4 T cells upon activation of the Syk pathway [28], leads to chromatin opening at the promoters of IL-17A and IL-17F through increased histone acetylation and reduced DNA methylation [29], and activates NF-κB [30]. The protein phosphatase (PP) 2A is increased in SLE T cells; it also controls the IL-17 promoter, inducing hypomethylation by suppressing the DNA methyltransferase 1 pathway, promoting acetylation of histone 3 [31,32], and facilitating the binding of IRF4 which is activated by Rho-associated protein kinase (ROCK)[33].…”
Section: Increased Numbers Of T Helper 17 Cells Promote Kidney Diseasmentioning
confidence: 99%
“…2). Stimulation of SLE T cells through TLR2, a molecule increased in SLE CD4 T cells upon activation of the Syk pathway [28], leads to chromatin opening at the promoters of IL-17A and IL-17F through increased histone acetylation and reduced DNA methylation [29], and activates NF-κB [30]. The protein phosphatase (PP) 2A is increased in SLE T cells; it also controls the IL-17 promoter, inducing hypomethylation by suppressing the DNA methyltransferase 1 pathway, promoting acetylation of histone 3 [31,32], and facilitating the binding of IRF4 which is activated by Rho-associated protein kinase (ROCK)[33].…”
Section: Increased Numbers Of T Helper 17 Cells Promote Kidney Diseasmentioning
confidence: 99%
“…Interleukin 17A is a multifunctional cytokine that impacts neutrophil recruitment, mediating both T-helper-1 (Th1) and T-helper-2 (Th2) cytokine production, and it possesses angiogenic properties through apoptosis modulation (3,12,13). IL-17A production, in vivo and in vitro, is primarily controlled by transforming growth factor beta 1 (TGF-β1) and interleukin 6 (IL-6) via the activation of signal transducer and activator of transcription 3 (STAT-3) in mouse and human models, respectively (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between certain genetic and environmental factors, including chemical factors, viruses and drugs, damages normal immune tolerance and contributes to SLE. Dysfunctional T cells interact with new antigens constantly, leading to a persistent autoimmune reaction (4,5). Previous studies have confirmed that the abnormal activation and proliferation of self-reactive cluster of differentiation (CD)4 + T lymphocytes have a central role in SLE.…”
Section: Introductionmentioning
confidence: 99%